Disturbia - Marcus, Jackie; Medjuck, Joe; Walsh, E. Bennett; Caruso, D.J.; Cold Spring Pictures; DreamWorks; Montecito Picture Company; Paramount Pictures ([California] : Dreamworks Home Entertainment, 2007)
After his father's death, Kale Brecht becomes a sullen, withdrawn, and troubled young man. He finds himself under a court-ordered sentence of house arrest after a run in with the law. His mother, Julie, works night and day to support herself and her son, only to be met with Kale's indifference and lethargy. As the walls of his house begin to close in on Kale, he turns into a voyeur as his interests turn outside the windows of his suburban home towards those of his neighbors. Slowly, Kale begins to suspect his neighbor is a serial killer
Title from title screen
Executive producers, Tom Pollock, Ivan Reitman ; director of photography, Rogier Stoffers ; edited by Jim Page ; music by Geoff Zanelli ; screenplay by Christopher Landon and Carl Ellsworth
Cast: Shia LaBeouf, Sarah Roemer, Carrie-Anne Moss, David Morse, Aaron Yoo, Jose Pablo Cantillo, Matt Craven, Viola Davis
DVD Format
With optional English, Thai, Korea, Mandarin, Cantonese or Bahasa Indonesian subtitles
Keywords: Home detention -- Drama; Voyeurism -- Drama; Criminal behavior -- Drama; Mothers and sons -- Drama